2002
DOI: 10.1074/jbc.m208882200
|View full text |Cite
|
Sign up to set email alerts
|

Dual-substrate Specificity Short Chain Retinol Dehydrogenases from the Vertebrate Retina

Abstract: Retinoids are chromophores involved in vision, transcriptional regulation, and cellular differentiation. Members of the short chain alcohol dehydrogenase/reductase superfamily catalyze the transformation of retinol to retinal. Here, we describe the identification and properties of three enzymes from a novel subfamily of four retinol dehydrogenases (RDH11-14) that display dualsubstrate specificity, uniquely metabolizing all-trans-and cis-retinols with C 15 pro-R specificity. RDH11-14 could be involved in the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
227
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(237 citation statements)
references
References 41 publications
(56 reference statements)
3
227
0
Order By: Relevance
“…Our findings are in agreement with previously published reports whereby RDH11, RDH12, RDH14 and RetSDR1 are shown to specifically prefer the phosphorylated coenzyme, and catalyze the reduction over the oxidation reaction (Haeseleer, Huang, Lebioda, Saari and Palczewski, 1998;Rattner, Smallwood and Nathans, 2000). RDH13 has been shown before to completely lack catalytic activity towards retinoids (Haeseleer, Jang, Imanishi, Driessen, Matsumura, Nelson and Palczewski, 2002) therefore it is not expected to contribute to the total RDH activity measured here. Our results in Figure 3A also show a low NAD/NADH-dependent activity suggesting either the presence of other and unknown RDHs in the microsomal fraction of 661W cells or that the existing RDHs can also use NAD and NADH but at a much lower efficiency than NADP/NADPH.…”
Section: Dehydrogenases In the 661w Cells Act As Reductases Rather Thsupporting
confidence: 94%
“…Our findings are in agreement with previously published reports whereby RDH11, RDH12, RDH14 and RetSDR1 are shown to specifically prefer the phosphorylated coenzyme, and catalyze the reduction over the oxidation reaction (Haeseleer, Huang, Lebioda, Saari and Palczewski, 1998;Rattner, Smallwood and Nathans, 2000). RDH13 has been shown before to completely lack catalytic activity towards retinoids (Haeseleer, Jang, Imanishi, Driessen, Matsumura, Nelson and Palczewski, 2002) therefore it is not expected to contribute to the total RDH activity measured here. Our results in Figure 3A also show a low NAD/NADH-dependent activity suggesting either the presence of other and unknown RDHs in the microsomal fraction of 661W cells or that the existing RDHs can also use NAD and NADH but at a much lower efficiency than NADP/NADPH.…”
Section: Dehydrogenases In the 661w Cells Act As Reductases Rather Thsupporting
confidence: 94%
“…8A). However, it was previously reported that human RDH14 has NADPH-dependent 11-cis retinal reductase activity (27). From this result, we thought that mouse RDH14 may also have an activity to produce 11-cis retinal from its retinol in the absence of aldehydes but in the presence of added NADP ϩ .…”
Section: Dual Mechanism Of Oxidation Of 11-cis Retinol In Cones: Aldementioning
confidence: 56%
“…7, recombinant RDH13L-His6 contains tightly bound NADP ϩ , not NADPH, at a molar ratio of almost 1:1 to RDH13L-His6. Other members of RDH family enzymes require exogenous NAD(H) or NADP(H) as a cofactor of the retinoid reduction/oxidation (27). Based on these findings, we propose that RDH13L catalyzes the AL-OL coupling using tightly bound NADP ϩ .…”
Section: Discussionmentioning
confidence: 97%
“…After in-gel trypsin digestion, the eluted tryptic peptides were examined by microsequencing by liquid chromatography-mass spectrometry to verify the identity of the recombinant Lrat fragment. The purified protein was used to immunize mice as described before (23), and the monoclonal antibody was produced by established methods (24). The antibody was tested for its specificity by immunocytochemical testing of the Lratϩ/ϩ and LratϪ/Ϫ mouse retinas.…”
Section: Methodsmentioning
confidence: 99%